The Role of Indigenous Peoples in Local Wisdom-Based Forest Management in Papua: Case Studies and Development Strategies - Eric Krisna Sandi (Journal of Horizon, 2024)
Nestled within the heart of Papua's lush forests lies a narrative of profound significance—the intertwining destinies of its indigenous inhabitants with their ancestral lands. This exploration unveils the pivotal role played by Papua's indigenous communities in local wisdom-based forest management. Against mounting environmental challenges like deforestation and climate change, their stewardship embodies a holistic ethos of sustainability, melding cultural heritage with resource conservation. Through empirical analysis and case studies, this study reveals the resilience ingrained within indigenous forest management practices, from Dani governance structures to Asmat agroforestry techniques. Furthermore, it explores the multifaceted implications of indigenous engagement, advocating for inclusive governance models that honor indigenous rights and foster community-driven sustainability. By amplifying indigenous voices and fostering interdisciplinary collaboration, this study advocates for a transformative shift in conservation discourse—one that recognizes indigenous wisdom as a cornerstone of environmental stewardship. In essence, it calls for a future where forests embody not only biodiversity but also indigenous heritage, fostering a harmonious coexistence between humanity and nature.